Balanced time perspective, time management disposition, and resilience: a moderated mediation model of academic performance - Li, Yan (Frontiers in Psychology, 2025)
ObjectiveTime perspective and time management disposition are critical factors influencing academic achievement. Although balanced time perspective (BTP) has been associated with adaptive functioning across various life domains, its relationship with academic performance remains underexplored. This study proposes a moderated mediation model to examine the link between BTP and academic performance.MethodsThe study included 1,076 high school students (448 boys and 628 girls), aged 15 to 19 years. Participants completed self-report questionnaires assessing BTP, time management disposition, and resilience in their classrooms. Academic performance was measured using standardized test scores routinely administered by the school. The valid data were analyzed using the PROCESS macro for SPSS.ResultsBTP positively predicted academic performance, with time management disposition mediating this relationship. The indirect effect was further moderated by resilience, demonstrating a stronger effect among students with higher resilience levels.ConclusionThese findings suggest that BTP may influence children’s academic performance and offer novel strategies for promoting academic achievement in high school settings. In addition, the findings highlight the importance of fostering psychological traits like resilience to enhance academic performance. Future studies could explore educational interventions aimed at developing BTP and resilience, thereby enhancing students’ psychological skills.